(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
COVID-19 based restrictions on places of worship and religious gatherings were present in 31 of 49 countries examined in Sub-Sharan Africa between 2019 and 2022. While patterns differed slightly across religious traditions, a majority of both Muslim-majority and Christian-majority countries enacted and enforced this type of restriction at some point during this period. In a large majority of these countries there was some resistance to the restrictions. By the end of 2022 all of them were lifted so these restrictions on places of worship and religious gatherings did not permanently impact religious freedom in the region and appear to be largely temporary government actions linked to the pandemic.